Current–voltage characteristics of armchair Sn nanoribbons. Issue 11 (25th September 2014) - van den Broek, B.; Houssa, M.; Pourtois, G.; Afanas'ev, V. V.; Stesmans, A.
<x xml:space="preserve">Abstract</x> Two‐dimensional group‐IV lattices silicene and germanene are known to share many of graphene's remarkable mechanical and electronic properties. Due to the out‐of‐plane buckling of the former materials, there are more means of electronic funtionalization, e.g. by applying uniaxial strain or an out‐of‐plane electric field. We consider monolayer hexagonal Sn (stanene) as an ideal candidate to feasibly implement and exploit graphene physics for nanoelectronic applications: with increased out‐of‐plane buckling and sizable spin–orbit coupling it lends itself to improved Dirac cone engineering. We investigate the ballistic charge transport regime of armchair Sn nanoribbons, classified according to the ribbon width W = {3m – 1, 3m, 3m + 1} with integer m. We study transport through (non‐magnetic) armchair ribbons using a combination of density functional theory and non‐equilibrium Green's functions. Sn ribbons have earlier current onsets and carry currents 20% larger than C/Si/Ge‐nanoribbons as the contact resistance of these ribbons is found to be comparable. (© 2014 WILEY‐VCH Verlag GmbH &Co. KGaA, Weinheim)